Determinants for intrinsically disordered protein recruitment into phase-separated protein condensates. Issue 2 (20th December 2021) - Jo, Yongsang; Jang, Jinyoung; Song, Daesun; Park, Hyoin; Jung, Yongwon
Abstract : Diverse interactions between folded and disordered proteins collectively dictate selective protein recruitment into bimolecular condensates. Abstract : Multivalent interactions between amino acid residues of intrinsically disordered proteins (IDPs) drive phase separation of these proteins into liquid condensates, forming various membrane-less organelles in cells. These interactions between often biased residues of IDPs are also likely involved in selective recruitment of many other IDPs into condensates. However, determining factors for this IDP recruitment into protein condensates are not understood yet. Here, we quantitatively examined recruitment tendencies of various IDPs with different sequence compositions into IDP-clustered condensates both in vitro as well as in cells. Condensate-forming IDP scaffolds, recruited IDP clients, and phase separation conditions were carefully varied to find key factors for selective IDP partitioning in protein condensates. Regardless of scaffold sequences, charged residues in client IDPs assured potent IDP recruitment, likely via strong electrostatic interactions, where positive residues could further enhance recruitment, possibly with cation–pi interactions. Notably, poly-ethylene glycol, a widely used crowding reagent for in vitro phase separation, abnormally increased IDP recruitment, indicating the need for careful use of crowding conditions. Tyrosines of IDP clients also strongly participated in recruitment both in vitro and in cells. Lastly, we measured recruitment degrees by more conventional interactions between folded proteins instead of disordered proteins. Surprisingly, recruitment forces by an even moderate protein interaction ( K d ∼ 5 μM) were substantially stronger than those by natural IDP–IDP interactions. The present data offer valuable information on how cells might organize protein partitioning on various protein condensates.